CUSTOMER ACCEPTANCE OF ROBOT SERVICE QUALITY AT KLUANG RAIL COFFEE - Zakariah, Siti Hajar; Hani, Shahrina; Mohd Nawi, Mohd Zulfakar (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The integration of robotics into the Malaysian food and beverage (F&B) sector has emerged as a promising innovation, particularly in enhancing operational efficiency and service quality. However, limited research explores customer acceptance of robotic services in this context. This study investigates customer perceptions of robotic service quality at Kluang Rail Coffee, Johor specifically assessing the impact of tangibility, reliability, responsiveness, assurance, and empathy on customer satisfaction. A quantitative approach was employed, collecting structured survey data from 267 respondents representing a broad demographic spectrum. The study found that tangibility, encompassing the robots’ appealing design and user-friendly features, was highly rated. Reliability, measured by task consistency and minimal malfunctions, also gained positive responses. Responsiveness, demonstrated by the robots’ promptness and adaptability, significantly influenced customer acceptance. Assurance, reflecting trust and confidence in robot service, emerged as a critical factor, while empathy, though limited by technological constraints, highlighted potential areas for future enhancement. Statistical analysis, including Spearman’s rank correlation, revealed a strong positive relationship between perceived service quality and customer acceptance. These insights offer practical implications for restaurant operators and policymakers seeking to optimize robotic services in Malaysian F&B settings. The study concludes that strategic improvements in service quality dimensions can drive greater acceptance, enhancing customer satisfaction and operational efficiency. Future research should explore AI-driven personalization to improve empathy in robotic interactions.